Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
This paper analyzes the implications of global rebalancing in the post-crisis period for Korea and how high leverage in the household and SMEs sectors could affect this process. The first section of the paper discusses implications of global rebalancing for Korea using simulations from the Global Integrated Monetary and Fiscal Model (GIMF). The second section focuses on how rebalancing growth in Korea is different from the rest of the region, and discusses the challenges of highly leveraged households and SMEs for the rebalancing process. The last section concludes with policy recommendations.